Maternal and Neonatal Outcomes in Pregnancies With Invasive Cancer [33L]. (May 2018) - Alpay Savasan, Zeynep; Zeb, Amna
Abstract : INTRODUCTION: To assess the maternal and neonatal outcomes in patients who had active cancer during pregnancy. METHODS: We reviewed the perinatal records of patients who had active cancer during or within the same year of pregnancy and delivered at Beaumont Health System between 2008 and 2017. We identified obstetrical maternal and neonatal adverse outcomes. RESULTS: There were total of 25 patients who had active cancer during pregnancy. These cancers include breast (n=12), lymphoma (n=5), uterine (n=2), malignant melanoma (n=1), acute myeloid leukemia (n=1), pancreas (n=1), colon (n=1), thyroid (n=1) and tongue (n=1). Among these patients 36% (9/25) had no maternal or neonatal complications, 28% (7/25) had both maternal and neonatal complications (spontaneous preterm delivery, gestational diabetes, thrombocytopenia, chorioamnionitis, low Apgar and meconium aspiration), 20% (5/25) had only maternal (epidural abscess, venous thrombosis, pulmonary embolism, hypertensive disorder of pregnancy, placental abruption and accreta), and 12% (3/25) had only neonatal (prematurity, small for gestational age, cleft palate and torticollis) complications. Patient with leukemia had termination of pregnancy. There were no neonatal or childhood cancers diagnosed among this group. The cancer type had no effect on identified perinatal complications. CONCLUSION: Patients with active cancer during pregnancy have an increased risk for perinatal complications. Due to the low prevalence of active cancer during pregnancy, a multicenter data analysis should be considered to confirm our data.